Øyvind Ravna; Clarifying legal relations and prescribing rules of use in reindeer husbandry areas. A study regarding use of land consolidation procedures - Torp, Eivind (Rangifer, 2010)
Rettsutgreiing og bruksordning i reindriftsområder. En undersøkelse med henblikk på bruk av jordskiftelovgivningens virkemidler. [Clarifying legal relations and prescribing rules of use in reindeer husbandry areas. A study regarding use of land consolidation procedures].